15. Acute and sub-chronic toxicities of phatra tricholes capsule in experimental animals - Tung, Tran Thanh; Binh, Nguyen Thanh; Hien, Dang Thi Thu (Tạp chí Nghiên cứu Y học, 2024)
Phatra Tricholes capsule is a multiplant production planned for dyslipidemia patients. Herein, we assessed the potential toxicity of Phatra Tricholes, applying the protocol of acute and sub-chronic oral administration in experimental animal models. According to the WHO guidelines, the acute toxicity study was conducted on Swiss mice. Sub-chronic toxicity studies were conducted in Wistar rats, and oral administration was done at 0.11 and 0.33 g/kg for 30 consecutive days. As a result, Phatra Tricholes capsule used for mice at the highest dose (19.58 g/kg b.w) did not express acute toxicity in mice. Regarding the subchronic toxicity test, after oral administration of Phatra Tricholes, hematological parameters, hepato-renal functions, and microscopic images of the liver and kidney were unchanged compared with the control group. In conclusion, the Phatra Tricholes capsule did not produce acute and subchronic toxicities in Swiss mice and Wistar rats.